THE İMPORTANCE OF TEACHİNG COMPOSİTİON AND İTS ROLE İN STUDENTS' CREATİVE ACTİVİTY (International conference on multidisciplinary science, 2024)
The composition course allows the student to think figuratively and develop creative imagination, to develop the skills of seeing beauty and news in life, to summarize events and events, and to describe inner feelings in artistic images.